Eggs as a Local Food Innovation and an Integrated Strategy for Stunting Prevention in Indonesia - Syahputra, Nico; Oktarina, Oktarina; Indriani, Anggi Dwi; Alhanannasir, Alhanannasir; Pramona, Leksa Sahara; Margareta, Siska; Chumaidi, Muhammad (JURNAL ILMIAH MAHASISWA, 2025)
Stunting remains a challenging chronic nutritional issue in Indonesia due to its significant impact on physical growth, cognitive ability, and the overall quality of human resources. Preventing this condition requires cross-sectoral interventions through innovative, nutrient-dense foods that are accessible to the community. Eggs, as a local source of high-quality animal protein with excellent biological value, hold great potential as a primary ingredient in supplementary foods for children. This study aims to integrate scientific research findings and national policies regarding the contribution of eggs in reducing stunting rates, as well as to assess the effectiveness of egg-based food innovations in child nutrition programs in Indonesia. The study employed a literature review method involving ten national and international articles published between 2018 and 2025. The results showed that consuming one egg per day for six months could increase children’s length-for-age z-score (LAZ) by 0.63 SD and reduce stunting prevalence by up to 47%. Local programs such as SETEL (Sehat dengan Telor) and combinations of mung bean juice with boiled eggs have been proven to improve children’s nutritional status in various regions. The synergy between local food innovations, nutrition education, and cross-sectoral policies serves as an effective strategy to accelerate sustainable stunting reduction.